Jual Beli Organ Dalam Manusia Untuk Kebutuhan Tranplantasi Dalam Pandangan Hukum Islam - Fawaid Fawaid (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
Transplantation is a medical procedure performed by moving healthy organs to replace damaged organs. Currently, transplantation has been very developed and used in various countries including Indonesia. Indonesia prohibits the sale and purchase of organs because the principle of freedom of contract in Indonesia is faced with ethics, religion and culture that influence it. Indonesia also has regulations related to transplantation, namely Law No. 36 of 2009 concerning Health and Government Regulation No. 18 of 1981 concerning Clinical Cadaveric Surgery and Anatomical Cadaveric Surgery and Transplantation of Human Body Organs or Tissues and several other Ministerial regulations, but some of these regulations are known to be incomplete and tend to be unclear because there is a blurring of norms in them. Until these regulations are no longer efficient to use anymore. So the government recently issued a regulation related to transplantation, namely PP No. 53 of 2021 concerning Organ and Tissue Transplantation. Learning from some of the previous problems and also the fact that transplantation is not only problematic in its regulation but also due to Islamic law factors. The questions raised in this research are first, how is the regulation of human organ transplantation in National law and Islamic law. Second, how is the legal expediency of human organ transplantation in the perspective of National law. This type of research is normative juridical with descriptive qualitative legal material analysis. With the results of the conclusion, first, Indonesia currently has regulations regarding transplants that are more complete and clear and have been correlated quite well even though not all provisions in Islamic law are adopted in it. Second, the current transplant regulation has also fulfilled the elements of expediency, the regulation does not conflict with the law above it.